Analysis of Physical Fitness of Volleyball Extracurricular Students at SMAN 3 Bengkulu Selatan - Zopan Sopyan; Rivaldo Fernando; M. Rahman Hapis J; Eggy Fikri Pratama; David Cahyono Putra; Dolly Apriansyah (Educative Sportive, 2025)
This study aims to analyze the physical fitness level of students participating in volleyball extracurricular activities at SMAN 3 Bengkulu Selatan. Physical fitness is a crucial factor in supporting students' athletic performance and health. This study employed a descriptive quantitative method with a survey approach. The subjects of the study were 30 students who are active members of the volleyball extracurricular team. The instrument used was the Indonesian Physical Fitness Test (TKJI) for the 16–19 age group, which covers five main physical components. The results showed that the students' physical fitness level is generally in the "Moderate" category (50%). The leg muscle power component was in the "Good" category, but the arm muscle strength and cardiovascular endurance components still need improvement. These findings indicate the need for more systematic and measurable training program modifications by integrating sport science principles. This research is expected to serve as a reference for coaches and the school in designing more effective sports training programs to improve students' future athletic performance.